Orientalisme Dan Upaya Dialog Antarperadaban - Mutiullah Mutiullah (Ulumuna, 2007)
Discourse about clash of civilization between West and East is forever interesting to discuss about. It is not only related to political and ideological matter but even more also to epistemological problems as foundation of forming a civilization. So far, both problems have been dominated by political and ideological prejudice in which West always finds itself superior and East inferior; West always shows itself as an ordinate and centrum, and considers East a subordinate and peripheral. Such prejudice then gets its theoretical justification through orientalits’ works. Construction of binary opposition presented and applied in their works indicates a failure of inter civilization dialogue. West views East through western cultural perspective, while East views West as an aggressor that eagerly want to dominate East. In the future, we need an inter civilization dialogue that founded on cultural honesty and openness, not on prejudice and historical trauma.